Uji Kinerja Burner LPG Mesin Stirling dengan Variasi Kosumsi Bahan Bakar - Mawardi; Jufrizal; Hidayah, Muhammad (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
This study focuses on testing the ability of the LPG burner used in the Stirling engine. The LPG burner combines the fuel flow rate, air flow rate, and flame to produce combustion. This test uses a modified burner and is analyzed by the water boiling test method. The study aimed to determine the thermal efficiency, fuel flow rate, and burner power of the Stirling engine LPG with variations in fuel consumption. Variations in the flow rate of LPG fuel are carried out using a conventional LPG gas burner and turning device with the minimum, medium, and maximum settings. The results showed that the three variations of the mass flow rate of fuel at the minimum conditions had higher efficiency and low fuel consumption, but the burner power produced was very low; namely, 1,714 kW, compared to the medium and maximum requirements. The thermal efficiency parameter value at the minimum condition is 49.91%, and fuel consumption is 0.000036 kg/second or equivalent to 1296 grams/hour. The maximum burner power produced during the test was 4,487 kW.